Hard x-ray photoemission study of Yb1−xZrxB12: the effects of electron doping on the Kondo insulator YbB12. (26th May 2017) - Rousuli, A; Sato, H; Iga, F; Hayashi, K; Ishii, K; Wada, T; Nagasaki, T; Mimura, K; Anzai, H; Ichiki, K; Ueda, S; Kondo, A; et al.
Abstract: We have carried out hard x-ray photoemission spectroscopy (HAXPES) of Yb1− x Zr x B12 ( 0 ⩽ x ⩽ 0.875 ) to study the effects of electron doping on the Kondo insulator YbB12 . The Yb valences of Yb1− x Zr x B12 at 300 K estimated from the Yb 3d HAXPES spectra decreased after substituting Yb with Zr from 2.93 for YbB12 to 2.83 for Yb0.125 Zr0.875 B12 . A temperature dependent valence decrease was found upon cooling for all doping concentrations. We found peak shifts of the B 1s and Zr 3d5/2, and Yb 3+ 4f spectra toward the deeper binding-energy with increasing Zr concentration, which indicates a shift of the Fermi level to the higher energy and that of the Yb 4f hole level close to the Fermi level, respectively, due to electron doping. These results qualitatively show the enhanced hybridization between the Yb 4f and conduction-band states with Zr substitution, consistent with magnetic susceptibility measurements.